Defensive and remedial liability - Steel, S (Oxford University Press, 2023)
This chapter considers the relationship between moral and legal liability to bear the cost of a remedial burden, and moral and legal liability to being harmed in self-defense and other defense. Despite the apparent disanalogies between these two domains of when harming another is not a wrong, the chapter argues that, fundamentally, the facts which ground the non-wrongfulness of the harm in each are the same or highly similar. The chapter proceeds by considering and rejecting various differences between self-defense and remedial action which might be thought, at the interpersonal and institutional level, to support a difference in normative grounding, such as time, the distinction between completed and non-completed wrongs, and the role of courts. Overall, it seeks to demonstrate the theoretical importance of reflecting on the normative relationship between defensive liability and remedial liability for philosophical accounts of remedies in private law.